Achalasia complicated with bilateral pneumonia and sepsis - Jelena Isaković; Ivana Spasojević; Stanislava Petrović; Ivan Ergelašev; Branislava Jorović; Dajana Lendak (Liječnički vjesnik)
Achalasia is a rare esophageal motility disorder that is mostly manifested by the basic triad of symptoms: dysphagia, regurgitation, and retrosternal pain. Patients often disregard the symptoms for years or are treated for overlapping conditions with similar symptoms, such as GERD, gastritis, or various lung diseases from asthma to obstructive pulmonary disease. A common complication is aspiration leading to pneumonia, and these patients often go from pulmonologists to gastroenterologists in search of a diagnosis and cure. This study presents the case of a patient treated for severe, rare complication of achalasia, megaesophagus and esophagopleural fistula. The case study highlights the importance of a multidisciplinary approach, choosing the right therapeutic approach, and objective assessment of the situation, when we decide on one option while another option arises as the only one that is sustainable. In this case it is a complex intensive care approach.